Feeling Under Stress “Like on a Production Line” as Thinking Is Not Your Job: Some Insights on Intention to Leave in Healthcare Services Work - Carreri, Anna; Toniolo, Valeria; Lonardi, Cristina (Italian Sociological Review, 2025)
Work-related stress, burnout, and job dissatisfaction are constantly growing phenomena in the Italian healthcare context, as well as in international healthcare systems, potentially leading to a significant loss in terms of human and financial capital. This article aims to shed light on the factors that fuel disaffection and alienation among frontline healthcare professionals in the Italian public healthcare system. The question is addressed through a qualitative case study of a specific group of frontline healthcare professionals who have been poorly explored in the literature to date – physiotherapists – within a territorial hospital in Northern Italy. Semi-structured interviews with all the physiotherapists working in the organizational case study were collected. Our detailed thematic analysis of the interviews revealed five main dimensions of quality of work life that can produce situations of disaffection and alienation: the emotional, organizational, relational, work-life balance, and symbolic dimensions. We argue that the mechanisms underlying the sense of alienation which may prompt physiotherapists to contemplate a change in company or profession are drawn from distinctive features of work in (healthcare) frontline services. The analysis sheds light on the fatigue of emotional overload; the marginal position of physiotherapists in the service triangle in the healthcare context, which is physician-centred; the intensification of work rhythms linked to Taylorization processes of the healthcare system; and interestingly, the lack of reward mechanisms – both material ones, in terms of flexible hours, conciliation policies, and training opportunities, and mainly in terms of symbolic and social recognition for intellectual labour of healthcare professionals, i.e. physiotherapists.